CUSTOM – A CONSTANT IN LAW - ENE-DINU, Cornelia Beatrice Gabriela (International Journal of Legal and Social Order, 2024)
Custom, also known as tradition or customary law, has played a fundamental role in the development of law over time, being considered one of the oldest formal sources of law. Although in many modern legal systems it no longer holds the same value or importance, the study of customs remains essential for understanding the formation of positive law and the national character of a legal system. An analysis of legal folklore, i.e., the study of customs, habits, and traditions from a legal perspective, allows for both the historical evolution of legal norms and the general principles of law of a community to be outlined. Through custom, societies established accepted and respected rules of conduct over generations, thus laying the foundation for the subsequent development of written legislation. Custom preceded written laws and represented a form of social regulation based on the unanimous acceptance of certain conduct norms. In the absence of a formal legislative system, communities turned to traditions and customs to regulate social relations and ensure stability and order. Before the advent of written laws, customs and traditions were the only means by which communities were organised.